Sustainable Pathways: CO2 Emissions, FDI, Trade, and Energy in Post-Communist Economies - Tichá, Lucie; Djalilov, Bekhzod; Salahodjaev, Raufhon; Allanazarova, Dilnoza (International Journal of Energy Economics and Policy, 2024)
This study explores the intricate interplay among CO2 emissions, economic development, foreign direct investment (FDI) inflows, trade, and energy consumption in post-communist republics spanning from 1995 to 2017. Utilizing a panel cointegration test, we unveil a profound and enduring relationship among these variables. Long-term elasticities are meticulously examined through Dynamic Ordinary Least Squares (DOLS) and Fully Modified Ordinary Least Squares (FMOLS) regressions, both of which consistently reveal a positive association between GDP per capita, FDI inflows, trade, energy consumption, and CO2 emissions per capita over the long term. Moreover, employing a panel causality test, our analysis identifies a robust unidirectional causality, specifically from CO2 emissions to energy consumption, signifying a pivotal link in the chain of influence (p<0.01). These findings shed light on the nuanced dynamics of CO2 emissions and their intricate connections with economic growth, foreign investments, trade, and energy usage in the post-communist context.